2000
DOI: 10.1111/j.1540-8159.2000.tb06772.x
|View full text |Cite
|
Sign up to set email alerts
|

Near Fatal Electrical Storm in a Patient Equipped with an Implantable Cardioverter Defibrillator for Brugada Syndrome

Abstract: A patient with Brugada syndrome experienced incessant ventricular fibrillation 7 years after implantation of an ICD. General anesthesia, fast ventricular pacing, bretylium, and atenolol infusion were ineffective; amiodarone infusion was started. After 190 defibrillation shocks over 36 hours, the electrical storm stopped. A multiorgan failure occurred as a complication of the electrical storm and necessitated prolonged reanimation. Thorough cardiac evaluation revealed no structural abnormality and the patient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…2,8 -11 The high mortality rate in patients suffering from ES might be related to progressive deterioration of cardiac function resulting from the direct cell injury effect caused by frequent shocks 33,34 ; additionally, prolonged exposure to low-output states may further compromise cardiac contractility and impair renal and hepatic function. 35 In our population, a direct effect of CA on the prevention of ES has been suggested by the evidence that ES recurred only in the case of acute failure of the procedure; on other hand, survival rates were significantly higher among patients who had undergone CA successfully. Therefore, the favorable impact on CD may be related in part to the prevention of ES; in fact, 4 of 8 patients with ES recurrence died because of the recurrent event, whereas the 4 survivors required an immediate surgical treatment.…”
Section: Impact On Overall Prognosismentioning
confidence: 97%
“…2,8 -11 The high mortality rate in patients suffering from ES might be related to progressive deterioration of cardiac function resulting from the direct cell injury effect caused by frequent shocks 33,34 ; additionally, prolonged exposure to low-output states may further compromise cardiac contractility and impair renal and hepatic function. 35 In our population, a direct effect of CA on the prevention of ES has been suggested by the evidence that ES recurred only in the case of acute failure of the procedure; on other hand, survival rates were significantly higher among patients who had undergone CA successfully. Therefore, the favorable impact on CD may be related in part to the prevention of ES; in fact, 4 of 8 patients with ES recurrence died because of the recurrent event, whereas the 4 survivors required an immediate surgical treatment.…”
Section: Impact On Overall Prognosismentioning
confidence: 97%
“…Actually, the authors are not aware of a single case of death occurring in a patient with the Brugada syndrome treated with an ICD. Chalvidan et al 11 reported a case of near-fatal electrical storm in a patient with an ICD, but the patient subsequently fully recovered. In addition, there is no doubt that most patients who have experienced the trauma of cardiac arrest will feel a greater sense of security after an ICD is implanted.…”
Section: Efficacymentioning
confidence: 99%
“…(2) Electrical storms of VF and polymorphic ventricular tachycardia (PVT) occurring within a few hours are not infrequently observed in the Brugada syndrome. [11][12][13][14] Arrhythmic storms may lead to multiple ICD discharges with various consequences: need for emergency hospitalization, psychological disorders, 15 proarrhythmia, 16 deleterious effect on cardiac function, 17 electromechanical dissociation, 18 and even death. 19 (3) Although the incidence of ICD related complications is low, it is far from nil.…”
Section: Limitationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The clinical characteristics and the variability of the typical ECG features under autonomic modulation indicate the potential role of the cardiac autonomic nervous system in the pathogenesis and arrhythmogenesis of BS. 12 Cardiac autonomic neuropathy (CAN) can be assessed using simple non-invasive tests: the Valsalva manoeuvre, beat-to-beat heart rate variation, postural fall in blood pressure, and the sustained handgrip test.…”
Section: Introductionmentioning
confidence: 99%